Synthesis and characterization of nickel zinc ferrite nanoparticles prepared by thermal treatment method - Poh, Lin Leng (2013)
Cubic structured nickel-zinc ferrite nanoparticles Ni1-xZnxFe2O4(x = 0, 0.25, 0.5, 0.75 and 1) have been synthesized by thermal-treatment method. The Fourier trans form in infrared spectroscopy was used to confirm the presence of metal oxide bands at all temperatures and the removal of organic matters at 873 K. The structure and particle size were characterized by X-ray powder diffraction and transmission electron microscopy. The magnetic properties were determined by vibrating sample magnetometer and electron paramagnetic resonance electron paramagnetic resonance at room temperature. By increasing the calcinations temperatures from 723 to 873 K showed an increase of the lattice parameter, the particles size, coercivity, saturation magnetization, peak to peak line width and the value of g- factor. When the concentration of Zinc increased; the lattice parameter increased while the particles size, coercivity, peak to peak line width and the value of g-factor decreased.